Nature and Antiquities The Making of Archaeology in the Americas - Kohl, Philip L.; Podgorny, Irina; Gänger, Stefanie (University of Arizona Press, 2014)
Nature and Antiquities analyzes how the study of indigenous peoples was linked to the study of nature and natural sciences. Leading scholars break new ground and entreat archaeologists to acknowledge the importance of ways of knowing in the study of nature in the history of archaeology.